A closer look at effects of martial arts involvement among youth. (1st January 2012) - Theeboom, Marc
The involvement of youth in martial arts is often described in controversial terms. While it has been associated with negative effects to personal and social well-being (in terms of aggressive and violent behaviour), there is also a belief that martial arts practice among youngsters can lead to positive socio-psychological outcomes. To date, research has not provided conclusive evidence that negative outcomes of martial arts involvement can be ruled out, nor has it produced convincing evidence to unconditionally support the positive effects. Based on the fact that contextual factors can be expected to have an impact on martial arts participation among youth, the present paper tries to emphasise the need for a discerned view of the paradox that seems to exist with regard to perceived or proclaimed effects of youth's involvement.